Arterial hypertension in postmenopausal women - Ergasheva Ma’mura Tashtemirovna; Kamolova Diyora Jamshedovna (Genius Journals, 2023)
The article is based on a survey of 40 women aged 50 to 60 in the postmenopausal period. Arterial hypertension was diagnosed in 29.8% postmenopausal women, arterial hypertension in 70.2% women, symptomatic in 30.8% women. In postmenopausal women, arterial hypertension may be accompanied by impaired calcium and lipid metabolism. It should be noted that these changes probably indicate a positive correlation between the ionized fraction of serum calcium and total cholesterol. These disorders are considered as one of the clinical manifestations of Uarterial hypertension in postmenopausal women and require the development of measures for its treatment and prevention
Keywords: Arterial hypertension; hypertension; menopause; postmenopause